The math teacher´s learning as a research field - Riscanevo Espitia, Lida Esperanza; Jiménez Espinosa, Alfonso (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This review article presents several ways to understand the math teacher's learning through the analysis of the research focus regarding the teacher. The meaning conferred to the teacher's learning is deepened from philosophical approaches; the problems derived from the perspectives on the field; the paradigms or conceptual frameworks of teacher training and general theories of learning. The objective consists of understanding the assumptions and conjectures that determine the math teacher's learning view through their research development. Finally, it is considered the sociocultural perspective as an emerging field of research development, where the knowledge of the teacher and the process of knowing attribute new meanings to the math teacher's learning.